Digital single-operator cholangioscope for endoscopic retrograde appendicitis therapy - Kong, Ling-Jian; Liu, Dan; Zhang, Ji-Yu; Ullah, Saif; Zhao, Lixia; Li, Deliang; Yang, Huiyu; Liu, Bing-Rong (Endoscopy, 2021)
Background This study aimed to investigate the diagnostic and therapeutic value of a digital single-operator cholangioscope (SOC) system for endoscopic management of acute appendicitis.Methods 14 patients with acute uncomplicated simple or supportive appendicitis were evaluated between November 2018 and September 2020. The diagnosis of acute appendicitis was confirmed by direct colonoscopy imaging and cholangioscope. The success rate of digital SOC-assisted endoscopic retrograde appendicitis therapy (ERAT), the procedure time, postoperative length of hospital stay, complications, and recurrence rate were recorded.Results Technical success rate was 100 %, with high quality imaging of the appendiceal cavity achieved using SOC in all 14 patients. The mean procedure time was 37.8 (standard deviation [SD] 22) minutes. All patients experienced immediate relief from abdominal pain after the procedure. Mean postoperative hospitalization was 1.9 (SD 0.7) days. No recurrence occurred during 2–24 months of follow-up.Conclusion Digital SOC-assisted ERAT provided a feasible, safe, and effective alternative approach for diagnosis and management of acute uncomplicated appendicitis without the need for X-ray or ultrasonic guidance.